Effect of ESG Score on Financial Risk in IDX ESG Companies - Arief Hadiwibowo; Dony Abdul Chalid (Green Publisher Indonesia, 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) scores on financial risk and stock investment performance of issuers listed on the IDX ESG index over the period 2017 to 2023. Using a quantitative approach, this study applies panel data regression analysis to explore the relationship between ESG scores and financial risk and stock risk. The variables analyzed include ESG score, Return on Assets (ROA), leverage ratio, corporate assets, earnings per share and book value per share. The research findings show that ESG score has a significant negative effect on financial risk, which means that the higher the ESG score, the lower the financial risk faced by the company. However, its effect on stock risk is not significant. The practical implication of this study is the importance of improving the quality of ESG scores as a strategy to mitigate financial risk and increase firm value. This study makes an original contribution by focusing on Indonesia's emerging capital market and highlighting the role of governance aspects in risk management, thus enriching ESG literature in the context of emerging economies and supporting ESG policy development in Indonesia.